Development and Validation of Digital Concept Maps Package for Online Economics Instruction in Senior Secondary Schools - Chinyelugo, Tochukwu C; Igbokwe, Uche L; Nji, Ifeyinwa I; Eneogu, Njideka D; Agah, John; Amedu, Amos Nnaemeka (Soedirman Economics Education Journal, 2024)
The use of computers in education and instruction is on the high side now given the recent crop of digital learners in this digital era. Technological-based learning is a way of pacifying the today’s technology-hungry learners. Therefore, this study was aimed at developing and testing the efficacy of Digital Concept Maps Package (DCMP) for online Economics instruction in senior secondary schools. The study was a research and development study that used quasi experimental pretest-posttest non equivalent control group design. The population of the study was 986 SS2 Economics students in Nsukka Local Government Area of Enugu state. The sample of the study consisted of 201 SS2 Economics students from six secondary schools in the zone. The instrument for data collection was Economics Achievement Test (EAT). The EAT was face validated by seven experts from University of Nigeria, Nsukka. EAT has a reliability index 0.72 using Kuder – Richardson (K-R). The experts also validated the developed DCMP using a Validation Rating Scale (VRS). The data analysis was done using Mean, Standard Deviation and ANCOVA. The findings of the study showed that experts’ validation ratings of DCMP were very high and that the students’ mean achievement score in DCMP group was significantly higher than that of their counterparts taught with lecture method in the control group. The researchers concluded that DCMP is very effective in enhancing students’ achievement in Economics. The implication of the findings is that both Economics teachers and students need to start using DCMP for online instruction in Economics for better students’ achievement.